PERNIKAHAN MAHASISWA: DAMPAK KELANGSUNGAN PERKULIAHAN DAN KEHARMONISAN KELUARGA - Ismail, Wisma; Rahman, Nur Azizah; Nasim, Abu Sahman (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2024)
This research aims to understand and analyze the reason why students decide to marry during their studies and to understand and analyze the impact of student marriage on the continuation of their studies and family harmony. This research is a qualitative study with a descriptive method, where data is obtained from primary and secondary source. The data collection techniques used are interviews and documentation. The result of this research indicate that reasons students decide to marry during their studies include feeling reay for marriage, adhering to islamic law to avoid the slander of adultery and due to “married by accident”. The impacts of students marriages during their studies include positive impacts on the continuation of their studies, such as support and motivation from their partner, increased enthusiasm for learning, personal growth, and avoiding immoral actions. The negative impacts on their studies include poor time management, inability to complete academic task optimally, and not being able to graduate on time.